1992
DOI: 10.1111/j.1365-2133.1992.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Elephantiasis nostras verrucosa: beneficial effect of oral etretinate therapy

Abstract: Elephantiasis nostras verrucosa is characterized by chronic secondary, non-filarial lymphoedema due to recurrent lymphangitis, dermal fibrosis, and epidermal changes consisting of hyperkeratotic, verrucous and papillomatous lesions. Histologically, there is pseudoepitheliomatous hyperplasia. Therapeutic efforts should aim to reduce lymph stasis, which will also lead to improvement of the cutaneous changes. In this study, rapid disappearance of the hyperkeratotic and verrucous lesions, remarkable flattening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
1
23
0
7
Order By: Relevance
“…Histological findings were also similar to those of reported by Zouboulis (4) and Stoberl (5, 6) as elephantiasis nostras venucosa except for deposits of hemosiderin. Zouboulis (4) suggested that functional incapacity of lymphatics, which are the major escape routes for excess proteins and fluids in tissues, causes a high interstitial protein concentration, causing fluid to be retained in tissues as a result of osmotic forces and resulting in chronic inflammatory changes with fibrosis and epidermal hyperplasia. One of the etiologies reported for this condition is chronic bacterial infection (1)(2)(3).…”
Section: Discussionsupporting
confidence: 90%
“…Histological findings were also similar to those of reported by Zouboulis (4) and Stoberl (5, 6) as elephantiasis nostras venucosa except for deposits of hemosiderin. Zouboulis (4) suggested that functional incapacity of lymphatics, which are the major escape routes for excess proteins and fluids in tissues, causes a high interstitial protein concentration, causing fluid to be retained in tissues as a result of osmotic forces and resulting in chronic inflammatory changes with fibrosis and epidermal hyperplasia. One of the etiologies reported for this condition is chronic bacterial infection (1)(2)(3).…”
Section: Discussionsupporting
confidence: 90%
“…Case reports of ENV evolving in the absence of cellulitis or lymphangitis exist. 6 Our study highlights the importance of two lesser appreciated factors in the setting of ENV, specifically obesity and CVI. All 21 patients were obese with 91% of them meeting criteria for morbid obesity (BMI $ 40).…”
Section: Discussionmentioning
confidence: 89%
“…Both topical and systemic retinoids have been successfully used to mitigate the cutaneous manifestations of ENV. 6,21 Two case reports illustrated favorable results with the use of scalpel debridement. 22,23 In one of these surgical reports, adjunctive dermabrasion with a motorpowered grinder was used.…”
Section: Discussionmentioning
confidence: 97%
“…Treatments for ENV include conservative measures to reduce lymphostasis (compressive stockings, mechanical massage), medical management of edema by diuretics, and prevention of recurrent infection by prolonged courses of antibiotics 2 . Oral retinoids may be effective, but the sustainability of these results appears variable 14 .…”
Section: Discussionmentioning
confidence: 99%